FOOD SECURITY ISSUES ON FACEBOOK: A DESCRIPTIVE STUDY OF THE ALGERIAN NATIONAL ORGANISATION FOR AGRICULTURE AND FOOD SECURITY’S PAGE DURING JULY 2024 - Nassira Djeghri Zarouta (Chelonian Research Foundation, 2025)
This study aims to address a scientific issue concerning the role of the National Organisation for Agriculture and Food Security in promoting awareness about food security through its Facebook page. The topic of food and its security has become a critical global issue due to health crises, wars, and conflicts, which have directly impacted food and water supplies. This research is part of descriptive-analytical studies, focusing on the role of new media in fostering food security culture, as communication tools have become remarkably widespread since the mid-2000s. The study reached several key conclusions, the most important being that the page heavily relies on videos accompanied by text. It predominantly uses the Arabic language, with its content leaning towards a scientific approach based on intellectual and cognitive appeals. The page focuses on economic objectives in promoting food security culture, with most posts related to food, agriculture, technology, and land reclamation.